Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1460-9592.2012.03807.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of moderate–severe pain in hospitalized children

Abstract: The prevalence of moderate-severe pain in hospitalized children remains high. Analgesia regimens may not be optimal. Underutilization of regional anesthesia techniques may have contributed to increased pain scores. A large proportion of children diagnosed with moderate-severe pain may have persistent clinically significant pain in subsequent days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 27 publications
3
92
1
10
Order By: Relevance
“…35 Taylor reported high pain prevalence rates for NICU patients (.90%), and both Birnie and Groenewald found infants to be a high-risk group for significant pain. 1,17,18 Many pain assessment tools are available for use on neonates and premature infants; it is plausible that use of different tools in a variety of settings is at least partially responsible for the variance in pain detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Taylor reported high pain prevalence rates for NICU patients (.90%), and both Birnie and Groenewald found infants to be a high-risk group for significant pain. 1,17,18 Many pain assessment tools are available for use on neonates and premature infants; it is plausible that use of different tools in a variety of settings is at least partially responsible for the variance in pain detection.…”
Section: Discussionmentioning
confidence: 99%
“…Yet despite these efforts, studies show that hospitalized children are still experiencing moderate to severe pain in high numbers. 1,[17][18][19][20][21][22] Additionally, review of our patient satisfaction data suggested we were not consistently meeting expectations with regard to pain management in our own institution.…”
mentioning
confidence: 99%
“…Hospitalised children regularly suffer from moderate to severe pain [1][2][3][4][5]. Sadly inadequate pain treatment shown in the 1980s and 1990s is still prevailing [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptación cultural y validación de contenido 1. Traducción: se reportaron algunas dificultades en los descriptores 2 -Fisgada, 6 -Repuxa y 18 -Espalha, pues no existe traducción exacta del descriptor para el español, pero se optó por elegir la palabra que más se aproximara a la palabra original del instrumento; el resultado fue: 2 -Tirón, 6 -Sacudida y 18 -Se extiende.…”
Section: Resultsunclassified
“…La prevalencia del dolor en la población pediátrica varía entre el 27 y el 87 %, donde los niños con diagnósticos quirúrgicos experimentan mayores niveles de dolor agudo en comparación con niños con diagnósticos médicos (1,2). Los niños hospitalizados con diagnósticos quirúrgicos generalmente poseen heridas derivadas de estos procedimientos, que generan dolor en respuesta a los daños tisulares ocasionados por fuerzas mecánicas, irritación química, daño vascular, inflamación o infección, además del propio tratamiento y de procedimientos relacionados con la herida (3,4).…”
Section: Introductionunclassified